2022
DOI: 10.3390/brainsci12060727
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Specific Analysis of the Dynamic Reconfiguration of the Brain in Patients with Schizophrenia

Abstract: The analysis of resting-state fMRI signals usually focuses on the low-frequency range/band (0.01–0.1 Hz), which does not cover all aspects of brain activity. Studies have shown that distinct frequency bands can capture unique fluctuations in brain activity, with high-frequency signals (>0.1 Hz) providing valuable information for the diagnosis of schizophrenia. We hypothesized that it is meaningful to study the dynamic reconfiguration of schizophrenia through different frequencies. Therefore, this study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…When looking into the alterations of our dynamic functional measures along the AD continuum, we observed that, in general, the flexibility was decreased in all the RSNs, with the exception of the SM network. This result concurs with previous research emphasizing the critical role of network flexibility in cognitive processing and the loss of this function in a variety of neurological disorders (19,22,23). In addition, across the AD continuum, the dynamic integration coefficient was increased in all RSNs, and the dynamic recruitment coefficient was either increased or maintained in most RSNs, except for the VIS network, which showed a decrease in recruitment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When looking into the alterations of our dynamic functional measures along the AD continuum, we observed that, in general, the flexibility was decreased in all the RSNs, with the exception of the SM network. This result concurs with previous research emphasizing the critical role of network flexibility in cognitive processing and the loss of this function in a variety of neurological disorders (19,22,23). In addition, across the AD continuum, the dynamic integration coefficient was increased in all RSNs, and the dynamic recruitment coefficient was either increased or maintained in most RSNs, except for the VIS network, which showed a decrease in recruitment.…”
Section: Discussionsupporting
confidence: 91%
“…Novel methods in network neuroscience, such as multilayer network modeling and multilayer community detection (18), have been used to analyze brain activity over time measured with fMRI in healthy individuals (19)(20)(21) and in patients with schizophrenia (22,23). This approach normally separates fMRI data into a number of time windows or snapshots and a correlation measure is used to build a functional network for each time window (24).…”
Section: Introductionmentioning
confidence: 99%